Coaches` satisfaction with their athletic partnerships - Lorimer, R. (International Journal of Coaching Science, 2009)
Coaches play a key role in the development of athletes, and the close relationships that they form can have a profound impact upon both partners (Jowett, 2007). One factor that has been linked with the quality of that relationship is satisfaction, a positive affective state based upon evaluation of related experiences. However, although athlete satisfaction has long been accepted as an important factor in performance (Chelladurai & Riemer, 1997), the area of coach satisfaction remains relatively unexplored. The present study explored the association between coach satisfaction, as measured by the adapted Athlete Satisfaction Questionnaire (Riemer & Chelladurai, 1998), and coaches` perceptions of the quality of their relationships with their athletes, as measured by the Coach-Athlete Relationship Questionnaire (Jowett & Ntoumanis, 2004). The results of these analyses showed that while relationship quality was a significant predictor of variance in coach satisfaction, different elements of the relationship influenced satisfaction to varying degrees. While relationship quality is evidently a factor in coach satisfaction, it is a complex, interdependent association that needs further exploration. Coach satisfaction remains an under explored area and an important line of future enquiry.